DAS01- Ammar Khammash: Notes on Formation - Majzoub, Raafat; Khammash, Ammar (Dongola Limited Editions; Dongola Publishing, 2022)
The first issue of the Dongola Architecture Series, dedicated to the most iconic contemporary architects of Arab culture, dives into the transdisciplinary perspective of Jordanian architect, artist and anthropologist Ammar Khammash. Notes on Formation is the first book in our Architecture Series, a platform to publish multi-layered readings of conversations with Arab architects working across the region's contemporary landscapes. Dongola's inquiry into architecture is rooted in the discipline's lack of discipline, in the way it generatively leaks into other fields as a true intersection of thought and practice. Architecture allows us to speak to the nature of our times, and in this case, the pertinence of our contemporary cultural production in expanding our world beyond current pessimism about the future.
English
Keywords: NA190-1555.5 History